Electrogenerated base-promoted cyclopropanation using alkyl 2-chloroacetates - Matsumoto, Kouichi; Hayashi, Yuta; Hamasaki, Kengo; Matsuse, Mizuki; Suzuki, Hiyono; Nishiwaki, Keiji; Kawashita, Norihito (Beilstein Journal of Organic Chemistry, 2022)
The electrochemical reduction conditions of the reaction of alkyl 2-chloroacetates in Bu4NBr/DMF using a divided cell equipped with Pt electrodes to produce the corresponding cyclopropane derivatives in moderate yields were discovered. The reaction conditions were optimized, the scope and limitations, as well as scale-up reactions were investigated. The presented method for the electrochemical production of cyclopropane derivatives is an environmentally friendly and easy to perform synthetic procedure.
Keywords: alkyl 2-chloroacetates; cyclopropane derivatives; divided cell; electro-reduction